2020
DOI: 10.1080/13573322.2020.1865905
|View full text |Cite
|
Sign up to set email alerts
|

Towards a culturally relevant sport pedagogy: lessons learned from African Australian refugee-background coaches in grassroots football

Abstract: There is a body of research that indicates the need for community-driven and culturally responsive pedagogies in sport-based interventions. There is much to learn from the pedagogical approaches and experiences of African Australian refugee-background coaches who work with refugee-background young people toward acceptance and affirmation of their cultural and racial identities. This paper explores African Australian refugee-background coaches' pedagogies in working with African Australian refugee-background yo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 36 publications
1
6
0
Order By: Relevance
“…The intention was for participants to feel empowered and motivated to participate constructively in their development because their voices are both sought and responded to. This required collective, mutual action and reflection on the part of both the researcher and the participants (for more information see Luguetti et al, 2020;Luguetti et al, 2021).…”
Section: Football Empowermentmentioning
confidence: 99%
“…The intention was for participants to feel empowered and motivated to participate constructively in their development because their voices are both sought and responded to. This required collective, mutual action and reflection on the part of both the researcher and the participants (for more information see Luguetti et al, 2020;Luguetti et al, 2021).…”
Section: Football Empowermentmentioning
confidence: 99%
“…Notably, the authors reported on a project that used volunteers/employees with a refugee background, which they considered of crucial importance when it came to supporting young refugees' sports participation and integration into multi-ethnic clubs (see also Mohammadi 2019). Taking the perspective of African Australian football coaches with a background as refugees, Luguetti et al (2020), too, described how such coaches could 'break barriers' and provide support to young people inside and outside of football. What is more, the coaches contributed towards creating a space for sharing personal experiences of social inequality; in this way the programme 'could be a vehicle of disrupting harmful public and media discourses around African Australian refugee-background young people' (Luguetti et al 2020, 10).…”
Section: Former Studies Of Refugees' Sports Participationmentioning
confidence: 99%
“…Our previous research has contributed to knowledge on cultural diversity, social inclusion, and social justice by examining barriers and facilitators to sport participation, processes of racialisation, racial ideologies, and anti-racism in diverse sport and physical education settings (e.g. McDonald and Spaaij, 2020;Luguetti et al, 2022a). Whilst this scholarship has been consistent with efforts to make the sociology of sport more central to analyses of social power (Eckstein et al, 2010;Karen and Robert, 2001), over time weindividually and collectivelyhave become increasingly committed to undertake research that can 'make a difference' beyond academia (Donnelly, 2015).…”
Section: Introductionmentioning
confidence: 99%